Elevation in troponin associated with COVID-19 is associated with an adverse long-term outcome. (2nd May 2022) - Deshpande, A; Bajomo, T; Rathod, KS; Baumbach, A; Mathur, A; Jones, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Aim: Elevated troponin levels have been shown to predict in-hospital outcomes in patients with COVID-19. However, whether this relates to or predicts longer-term outcomes is unknown. We aimed to investigate the effect of troponin elevation in patients with COVID-19, looking at resource utilisation post discharge, re-hospitalisation and outcomes. Methods: This was a prospective study of 7650 patients admitted from December 2019 to July 2020 across a large university hospital trust. Patients were stratified according to COVID-19 status and troponin values (elevated = troponin T ≥15 ng/mL). The primary outcome assessed was all-cause mortality. Results: 1005 patients were COVID-19 positive and had elevated troponin levels, with the remaining patients troponin positive but COVID-19 negative. COVID+ patients were more likely to be older, and less likely to be Caucasian (35.7% vs 46.6%, p<0.0001), however, peak troponin did not differ significantly between the groups {54 (28-125) vs 47 (25-130) ng/mL, p=0.121}. Mortality before first discharge was four times more likely in COVID+ than COVID- patients with elevated troponins {389 (39%) vs 359 (9.9%); p<0.001}. This mortality rate was also significantly higher than in COVID-19 positive patients who were troponin negative (p=6%, P<0.0001). Post-discharge over a follow-up period of 365 days, in the discharged COVID-19 positive troponin positive group, a minority of patients (13.2%) were investigated with outpatient cardiac investigations (echocardiography, CTCA, coronary angiography and cardiac MRI) compared to the COVID-19 negative group (34.5%). Post-discharge mortality was significantly higher among the COVID+ cohort {63 (10.2%) vs COVID-19 negative troponin positive 103 (3.1%); p<0.001}. COVID+ patients who died post discharge were more likely to be Caucasian (55.4% vs 35.2%, p<0.05) and more likely to be older (81 (72-87.5) vs 67 (57-79), p<0.05) than COVID+ patients who survived post discharge. Conclusion: Elevated troponin levels in patients with COVID-19 is associated with long-term mortality. Patients were unlikely to undergo cardiac investigations and the troponin rise likely reflects illness severity. Further data is needed in this area.